1982
DOI: 10.1021/jf00112a016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of limonin in the fruit tissues of nine grapefruit cultivars

Abstract: This report presents the results of a study conducted to determine the distribution of limonin within the fruit tissues of nine grapefruit cultivars. It was found that the highest limonin levels within the fruit tissues were found in the cotyledon, followed by inner seed coat, outer seed coat, central pith, segment membrane, albedo and flavedo, and juice vesicles, in decreasing amounts. The concentration of limonin in the tissues of the individual cultivars is also presented, and the variation in limonin conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 3 publications
2
18
1
Order By: Relevance
“…Compared with the previous report, the deceasing degrees of limonin in different tissues followed the order of segment membranes > albedo > flavedo > juice vesicles (McIntosh et al, 1982). While in our study, the deceasing degrees of limonin followed the order of segment membranes > albedo > juice sacs > flavedo.…”
Section: Relationships Between the Three Bitter Compounds In Fruit Ticontrasting
confidence: 73%
“…Compared with the previous report, the deceasing degrees of limonin in different tissues followed the order of segment membranes > albedo > flavedo > juice vesicles (McIntosh et al, 1982). While in our study, the deceasing degrees of limonin followed the order of segment membranes > albedo > juice sacs > flavedo.…”
Section: Relationships Between the Three Bitter Compounds In Fruit Ticontrasting
confidence: 73%
“…Limonin occurs at the highest concentrations in the cotyledon. It also is present in the seed coat, pith, segment membranes, albedo, flavedo, and juice vesicles in order of decreasing concentration (McIntosh et al 1982). Naringin ( Fig.…”
Section: Citrus Fruitsmentioning
confidence: 98%
“…Results from a previous study of the distribution of limonin in grapefruit tissues of nine grapefruit cultivars showed that the concentration range within each tissue varied more than 10-fold (McIntosh et al, 1982). The observed ranges in concentration could be due to random events.…”
Section: Introductionmentioning
confidence: 85%
“…This compound has been one of the most extensively studied of the limonoids due to its abundance and its importance in processed citrus fruit, especially juices. Previous studies have shown that lemon, C. limon, leaves are able to synthesize limonin from nomilin, and ultimately this compound or its nonbitter precursor, limonoate A-ring monolactone, is subsequently transported to the fruit where it accumulates in the seeds, carpellary membranes, and the central pith (Hasegawa and Hoagland, 1977;Hasegawa et al, 1980Hasegawa et al, , 1986McIntosh et al, 1982;Ronneberg et al, 1995).…”
Section: Introductionmentioning
confidence: 99%